2013
DOI: 10.1002/jgre.20157
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the subsurface structure of the Caloris basin, Mercury, from assessments of mechanical layering and changes in long‐wavelength topography

Abstract: [1] The volcanic plains that fill the Caloris basin, the largest recognized impact basin on Mercury, are deformed by many graben and wrinkle ridges, among which the multitude of radial graben of Pantheon Fossae allow us to resolve variations in the depth extent of associated faulting. Displacement profiles and displacement-to-length scaling both indicate that faults near the basin center are confined to a~4-km-thick mechanical layer, whereas faults far from the center penetrate more deeply. The fault scaling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 85 publications
(135 reference statements)
0
11
1
Order By: Relevance
“…2 are consistent with this pattern. However, the amplitude of dynamic topography predicted by models with these patterns is one to two orders of magnitude 43 below that of observed undulations 41 . The origin of Mercury's long-wavelength warping thus remains unclear.…”
Section: Kinematics Of Shortening-related Deformationmentioning
confidence: 74%
See 2 more Smart Citations
“…2 are consistent with this pattern. However, the amplitude of dynamic topography predicted by models with these patterns is one to two orders of magnitude 43 below that of observed undulations 41 . The origin of Mercury's long-wavelength warping thus remains unclear.…”
Section: Kinematics Of Shortening-related Deformationmentioning
confidence: 74%
“…However, the horizontal strains accommodated by folds of such observed wavelengths and amplitudes may be of the order of 10 −5 (ref. 41), so their contribution to planetary radius change would be minor compared with that of the faultrelated structures. Such buckling on Earth and presumably Mercury requires compressional stresses that substantially exceed the elastic strength of the lithosphere.…”
Section: Kinematics Of Shortening-related Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…This peculiar distribution of the pyroclastic deposits may reflect their relatively young age [ Thomas et al , ] with respect to the effusive volcanism that fills the entire basin [ Ernst et al , ]. In fact, the subsurface structure of the Caloris basin should have many faults that penetrate deeper into the interior of Mercury at the edge of the basin [ Klimczak et al , ], thus favoring a deeper source for explosive volcanism, as often suggested for the Moon [ Gaddis et al , ]. Klimczak et al [] also suggests that the center part of Caloris, Pantheon Fossae, is most likely to have been formed as the result of doming in the central part, probably caused by a magma chamber.…”
Section: Mercury's Volcanismmentioning
confidence: 99%
“…They interpreted this to be a volcanic construct (Prockter et al, 2010). Smooth plains materials in and around Caloris basin are also interpreted to be volcanic ; recent studies Klimczak et al, 2013) suggest that the volcanic fill within the Caloris basin is about 2.5-4.0 km thick.…”
Section: Mercury Volcanismmentioning
confidence: 94%